2018
DOI: 10.1007/s00240-018-1059-5
|View full text |Cite
|
Sign up to set email alerts
|

Journey of a cystinuric patient with a long-term follow-up from a medical stone clinic: necessity to be SaFER (stone and fragments entirely removed)

Abstract: There is a lack of studies looking at the longitudinal follow-up of patients with cystine stones. We wanted to assess the journey of cystinuric patients through our specialist metabolic stone clinic to improve the understanding of episodes, interventions and current outcomes in this patient cohort. After ethical approval, all patients who attended our metabolic stone clinic from 1994 to 2014 with at least one cystine stone episode were included in our study. Data were retrospectively analysed for patient demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
(38 reference statements)
0
26
0
Order By: Relevance
“…Surgical management of cystine renal stones does not differ significantly from other stone compositions [51][52][53] . However, due to frequent recurrent episodes, complete stone clearance is of importance where possible to avoid growth of residual fragments which may result in symptoms or further surgery later 54 . Small renal stones may be observed with periodic evaluation as they may pass.…”
Section: Statementsmentioning
confidence: 99%
“…Surgical management of cystine renal stones does not differ significantly from other stone compositions [51][52][53] . However, due to frequent recurrent episodes, complete stone clearance is of importance where possible to avoid growth of residual fragments which may result in symptoms or further surgery later 54 . Small renal stones may be observed with periodic evaluation as they may pass.…”
Section: Statementsmentioning
confidence: 99%
“…24 Stone free rates ranged from 22 to 87% with diuresis, alkalization and pharmacological management after single or multiple surgical procedures. 11, 17, 19, 25, 27, 29, 30, 32 Thiol-treated patients had decreased stone recurrence when urinary cystine excretion was maintained at <797 mg/gm creatinine/24 hours. 25…”
Section: Resultsmentioning
confidence: 98%
“…10, 11, 17-20, 23-34 20 studies reported outcomes from surgical interventions in cystinuria patients. 10, 11, 17-20, 24-26, 29, 30, 32-40 Of the 24 studies, 15 reported combined intervention methods with alkalinizing compounds, pharmacological drugs and/or surgical procedures. 10, 11, 17-20, 24-27, 29, 30, 32-34 No studies directly compared pharmacological intervention to surgical intervention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations